Evaluation of maize genotypes for resistance to maydis leaf blight and charcoal rot under artificial epiphytotic conditions - J.S. CHAWLA, HARLEEN KAUR*, N.S. MALHI (Indian Phytopathology, 2010)
Twenty maize inbred lines were evaluated against maydis leaf blight (Drechslera maydis) and charcoal rot (Macrophomina phaseolina) under artificial epiphytotic conditions during monsoon 2005 and 2006. The severity of maydis leaf blight and charcoal rot was recorded following 1-5 and 1-9 scale respectively and the genotypes screened were grouped into three categories viz; resistant, moderately resistant and susceptible based on their disease reaction. Our results indicated that one genotype E-10 (LET DR99 x Ent 49-2) was resistant and five genotypes (E1, E2, E8, E9, E15) were moderately resistant to both the diseases. These resistant genotypes can further be utilized as donors in the breeding programmes. Â